Recent progress in biodegradable polymers and nanocomposite-based packaging materials for sustainable environment - Wroblewska-Krepsztul, Jolanta; Rydzkowski, Tomasz; Borowski, Gabriel; Szczypinski, Mieczysław; Klepka, Tomasz; Thakur, Vijay Kumar (Taylor and Francis, 2018)
Plastic-based materials are frequently used in packaging and can be seen universally in both the developed and developing societies. At present, most of the currently used food packaging materials are nondegradable and are creating serious environmental problems. New technologies are being explored and developed to study the complex interaction between the food packaging materials and food. For example, nanocomposite of cellulose constitutes environmentally friendly packaging, which is easily recycled by combustion and requires low power consumption in production. There are several such biodegradable materials which are available at a low price, have good mechanical properties and allow disposal in the soil. This is advantageous because biological degradation produces only carbon dioxide, water, and inorganic compounds to name a few. It has also been discovered that biodegradable plastics made of such materials can be disposed of together with organic waste. The widespread use of biopolymers in the place of standard plastics would help to reduce the weight of waste. Therefore, biodegradable materials take part in the natural cycle “from nature to nature” and play an important role for environmental sustainability. So, in this article, we briefly summarize the different characteristic of biodegradable polymers being used in food packaging applications.
Keywords: Biodegradation; packaging materials; plastic; polymer; wastes